2021
DOI: 10.1002/lary.29388
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Children who are Deaf or Hard‐of‐hearing: A Scoping Review

Abstract: Objective/Hypothesis: The goal of this scoping review is to evaluate and synthesize the published research regarding bullying and children who are deaf or hard-of-hearing (DHH).Study Design: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping review (PRISMA-ScR) statement was used as the guideline for conducting this review.Methods: This review included studies assessing pediatric (0-21 years) DHH children. Seventy records underwent the initial title-abstract screening,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…The magnitude of the effect size was calculated using the Hodges-Lehmann estimate, which uses the median differences between the two groups through the biserial rank correlation (r b ), interpreting an effect size as irrelevant if it is <0.1; small (0.1); medium (0.3) and large 0.5 [ 38 ]. In this case, we found in item Cpe.2 a statistically significant difference with an association strength close to a medium-size value (r b = 0.22) between the female gender and the perception that support for specific needs of students is a task for support specialists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the effect size was calculated using the Hodges-Lehmann estimate, which uses the median differences between the two groups through the biserial rank correlation (r b ), interpreting an effect size as irrelevant if it is <0.1; small (0.1); medium (0.3) and large 0.5 [ 38 ]. In this case, we found in item Cpe.2 a statistically significant difference with an association strength close to a medium-size value (r b = 0.22) between the female gender and the perception that support for specific needs of students is a task for support specialists.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies [ 38 , 39 , 40 ] have reported a significant association between SEN students and bullying at the school. Our study highlights that there is not a clear, direct relation between SEN and victimization; 38.9% of the teachers considered that SEN students might be bullied to a greater degree due to their characteristics than their peers, but 28% believe that victimization does not have to be associated with SEN, and 33.1% did not show a specific perception about it (Mdn: 80.7).…”
Section: Discussionmentioning
confidence: 99%
“…Las consecuencias de este fenómeno han sido ampliamente documentadas y van desde afectaciones académicas como la deserción escolar, bajo rendimiento escolar, hasta desajustes de carácter psicosocial y trastornos psicopatológicos (Gutiérrez, 2018), entre los que resaltan el consumo de sustancias psicoactivas, ansiedad, estrés, trastornos del sueño (Bouldin et al, 2021), depresión (Dervishi, et al, 2019), suicidio (Midgett & Doumas, 2019 y los trastornos de la conducta alimentaria (Buendía et al, 2016). Estos impactos pueden llegar a producirse independientemente del rol de víctima, agresor, agresor-victimizado o espectador, convirtiéndose en un factor de riesgo para la salud mental del individuo (Aguirre-Flórez et al, 2015;Midgett & Doumas, 2019).…”
Section: Palabras Claveunclassified
“…Deaf and hard of hearing (DHH) adolescents and children wearing visible hearing devices face more peer victimization and/or bullying in schools because of being considered different from their normal-hearing peers. [9,10] Swearer et al [11] reported that adolescents or children who have an observable disability such as wearing hearing devices are more likely to be involved in peer victimization and/or bullying (89.9%) than their normal-hearing peers (72.2%). [12] Furthermore, Armitage [13] reported nearly one-third (32%) of all children worldwide have experienced victimization and/or bullying once or more within the past month, and almost one in thirteen (7.3%) have been bullied six or more times.…”
Section: Introductionmentioning
confidence: 99%